Identification, evolution, expression and protein interaction analysis of genes encoding B-box zinc-finger proteins in maize - Xiao-hui XU; Wen-lan LI; Shu-ke YANG; Xiang-zhen ZHU; Hong-wei SUN; Fan LI; Xing-bo LU; Jin-jie CUI (Journal of Integrative Agriculture, 2023)
The B-box (BBX) family of proteins consists of zinc-finger transcription factors with one or two highly conserved B-box motifs at their N-termini. BBX proteins play crucial roles in various aspects of plant growth and development, including seedling photomorphogenesis, shade avoidance, flowering time, and biotic and abiotic stress responses. Previous studies have identified many different BBXs from several plant species, although the BBX family members in maize are largely unknown. Genome-wide identification and comprehensive analysis of maize BBX (ZmBBX) expression and interaction networks would therefore provide valuable information for understanding their functions. In this study, 36 maize BBXs in three major clades were identified. The ZmBBXs within a given clade were found to share similar domains, motifs, and genomic structures. Gene duplication analyses revealed that the expansion of BBX proteins in maize has mainly occurred by segmental duplication. The expression levels of ZmBBXs were analyzed in various organs and tissues, and under different abiotic stress conditions. Protein–protein interaction networks of ZmBBXs were established using bioinformatic tools and verified by bimolecular fluorescence complementation (BiFC) assays. Our findings can facilitate a greater understanding of the complexity of the ZmBBX family and provide novel clues for unravelling ZmBBX protein functions.